The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/acem.14002
|View full text |Cite
|
Sign up to set email alerts
|

Interrupted Time Series of User‐centered Clinical Decision Support Implementation for Emergency Department–initiated Buprenorphine for Opioid Use Disorder

Abstract: Objectives Adoption of emergency department (ED) initiation of buprenorphine (BUP) for opioid use disorder (OUD) into routine emergency care has been slow, partly due to clinicians’ unfamiliarity with this practice and perceptions that it is complicated and time‐consuming. To address these barriers and guide emergency clinicians through the process of BUP initiation, we implemented a user‐centered computerized clinical decision support system (CDS). This study was conducted to assess the feasibility of impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…However, 1 study found that the rate of ED-initiated buprenorphine only increased when waivered providers also received a clinical decision support system and just-in-time training. 27 Recently trained ED providers are also more likely to believe OUD is similar to other chronic diseases and approve of ED-initiated buprenorphine, highlighting the importance of education in expanding prescribing capacity. 6 Third, interviewees argued that transitions of care for patients with OUD should mirror other ED referrals for high-risk conditions with many suggesting the establishment of a central agency to streamline communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 1 study found that the rate of ED-initiated buprenorphine only increased when waivered providers also received a clinical decision support system and just-in-time training. 27 Recently trained ED providers are also more likely to believe OUD is similar to other chronic diseases and approve of ED-initiated buprenorphine, highlighting the importance of education in expanding prescribing capacity. 6 Third, interviewees argued that transitions of care for patients with OUD should mirror other ED referrals for high-risk conditions with many suggesting the establishment of a central agency to streamline communication.…”
Section: Discussionmentioning
confidence: 99%
“…not yet have the capacity to schedule appointments.Previous work has leveraged the EHR to provide computerized clinical decision support systems, which have improved rates of buprenorphine prescribing in the ED for patients with untreated OUD 27. Additionally, patient privacy regulations surrounding health information, including patient records for the treatment of substance use disorders as guided by the 42 CFR Part 2 regulations, have recently been revised to facilitate coordination of care 29.…”
mentioning
confidence: 99%
“…To address this, one can benefit from points of access to patients to potentially initiating treatments. These include ED visit/hospital admission [ 138 , 139 , 140 , 141 , 142 ] and incarceration [ 143 , 144 , 145 , 146 , 147 , 148 , 149 ]. Employing techniques like screening, brief intervention, and referral to treatment (SBIRT) can also be helpful in this regard [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 However, a group at Ochsner Clinic demonstrated that the implementation of such a tool in 36 clinics greatly increased the number of patients receiving OUD therapy, and a group at the University of Texas Southwestern has been testing whether an OUD CDS can increase the initiation of buprenorphine treatment in emergency departments. [15][16][17][18] A National Institute on Drug Abuse Center for the Clinical Trials Network (CTN) report in 2020 concluded that a CDS tool for OUD screening, assessment, and treatment might help address the opioid crisis. 19 Our team has extensive experience with building and testing CDS systems and has been working on a version aimed at the CTN recommendations.…”
Section: Introductionmentioning
confidence: 99%